2021
DOI: 10.3390/polym13132067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Radiation on Optical Properties and Hardness of Transparent Wood

Abstract: Optically transparent wood is a type of composite material, combining wood as a renewable resource with the optical and mechanical properties of synthetic polymers. During this study, the effect of monochromatic UV-C (λ—250 nm) radiation on transparent wood was evaluated. Samples of basswood were treated using a lignin modification method, to preserve most of the lignin, and subsequently impregnated with refractive-index-matched types of acrylic polymers (methyl methacrylate, 2-hydroxyethyl methacrylate). Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Exposure to UV–C strongly affects the color and transmittance of transparent wood in a matter of days. Upon irradiation, TW acquires a yellow color, which darkens with increasing exposure time due to the reactivation of chromophores of residual lignin as well as the degradation of the impregnating polymer . To allow the application of transparent wood in buildings, e.g., as windows and roofs, it is of great importance to increase its resistance against environmental degradation (especially the UV light-induced one) and yellowing.…”
Section: Transparent Woodmentioning
confidence: 99%
“…Exposure to UV–C strongly affects the color and transmittance of transparent wood in a matter of days. Upon irradiation, TW acquires a yellow color, which darkens with increasing exposure time due to the reactivation of chromophores of residual lignin as well as the degradation of the impregnating polymer . To allow the application of transparent wood in buildings, e.g., as windows and roofs, it is of great importance to increase its resistance against environmental degradation (especially the UV light-induced one) and yellowing.…”
Section: Transparent Woodmentioning
confidence: 99%
“…With good thermal stability, up to 315 °C, TWCs can be designed to filter out UV-B radiation and have potential applications in smart building technology, especially in smart windows [ 172 , 173 ]. However, even with the chromophoric lignin fraction partially removed, TWCs still undergo some photo-discolouration and degradation on extended exposure to solar UV radiation [ 174 , 175 ]. This technical drawback, however, can be addressed with existing UV stabiliser technologies.…”
Section: Natural and Synthetic Materialsmentioning
confidence: 99%
“…Cai et al (2021) found that the yellowness of TW increased after the addition of ethylene glycol to the epoxy-impregnated wood to produce flexible TW [ 15 ]. The study showed that Tilia americana was delignified and poly methyl methacrylate (PMMA) was impregnated and then irradiated with UV-C (250 nm), and within a few hours of irradiation, discoloration of residual lignin towards yellow was observed with reduced transmittance [ 16 ]. The other study used Pinus sylvestris and Prunus serotina for delignification and epoxy impregnation to produce TW, and the TW kept in an outdoor condition was found to have undergone a color change towards yellow [ 17 ].…”
Section: Resultsmentioning
confidence: 99%